2018
DOI: 10.1038/s41598-018-28239-7
|View full text |Cite
|
Sign up to set email alerts
|

ETV1 activates a rapid conduction transcriptional program in rodent and human cardiomyocytes

Abstract: Rapid impulse propagation is a defining attribute of the pectinated atrial myocardium and His-Purkinje system (HPS) that safeguards against atrial and ventricular arrhythmias, conduction block, and myocardial dyssynchrony. The complex transcriptional circuitry that dictates rapid conduction remains incompletely understood. Here, we demonstrate that ETV1 (ER81)-dependent gene networks dictate the unique electrophysiological characteristics of atrial and His-Purkinje myocytes. Cardiomyocyte-specific deletion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 86 publications
2
19
0
Order By: Relevance
“…The split ratio was 1:3-1:6. The detailed differentiation protocol was described in the previous published reports [31,32]. Briefly, iPSC were…”
Section: Cell Culture and Differentiation Assaymentioning
confidence: 99%
“…The split ratio was 1:3-1:6. The detailed differentiation protocol was described in the previous published reports [31,32]. Briefly, iPSC were…”
Section: Cell Culture and Differentiation Assaymentioning
confidence: 99%
“…Because of different experiment conditions, data points need to be adjusted for two reasons before usage: temperature adjustment from room temperature to body temperature, and time adjustment for the shifted activation and inactivation curve along with time after the patch rupture. Therefore, the experiment data from Shekhar et al and Cerrone et al [9], [10] were first adjust with +12 mV from room temperature to body temperature (the V1/2 of the activation gate was moved from -57 mV at 16 ℃ to -49 mV at 26 ℃ reported by Murray et al [11], and linearity of the change was assumed). Then the data from Shekhar et al was further moved by +1.6 mV since the average patch life in their experiments was 15 min and it was reported that in guinea pig atria the activation curve of FSC move about +3.2 mV per 1/2 hour [12].…”
Section: Model Developmentmentioning
confidence: 99%
“…It has been found in experiments that the conductance of FSC in atria is bigger than that in ventricles. The maximum conductance was 1.14 ± 0.07 nS/pF in right atria and 0.92 ± 0.04 nS/pF in ventricles [9]. Also considering the maximum upstroke velocity should be around 200 V/s and the overshoot about +20 mV, we set the conductance of the FSC to 1.2 nS/pF at room temperature.…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart failure (HF) is the most popular chronic disease among the elderly 79 in developed countries (1), and its prevalence and incidence is increasing 80 in the resent years (2-4). Approximately 26 million individuals are 81 suffering HF worldwide (5), in which the survival rate within 5 years of 82 admission was less than 53% (6-8). The chronic heart failure causes a 83 tremendous economic burden with an estimation of $108 billion per year 84 globally (9).…”
Section: Introduction 78mentioning
confidence: 99%